Risk factors of death among children with Dengue Hemorrhagic fever - Nawing, Herry D; Pelupessy, Nini Meutia; Sabir , Merry; Albar, Husein (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Background: Dengue hemorrhagic fever (DHF) is still periodically around developing countries including Indonesia. Morbidity and mortality of DHF can be reduced if early diagnosis and appropriate management. Objective: Our study evaluate risk factors of death in pediatric DHF patients hospitalized in Wahidin Sudirohusodo Hospital Makassar. Methods: we review the medical records of patients aged ≤ 18 years from January 2016 to December 2018 with confirmed DHF based on WHO criteria and serologically positive anti-dengue Ig M or positive anti-dengue IgM and Ig G. Results: During the study period, 70 patients aged 1-17 years with the complete medical records enrolled in this study. The DHF severity consisted of 37 cases (52,9%) with shock(DSS) and 33 cases (41,7%) without shock and mostly of them was admitted to the hospital on > 3 days of fever (63 cases /90,0%). Boys were predominantly (39/55,7%) found than girls (31/44,3%) and the majority of cases above 5 years (50/71,4%) with well-nourished patients in 46 cases (65,7%). The hematocrit level ≥ 40 mg/dl, platelets ≤ 40.000/mm3, and leukocyte ≤ 4000 mm3/l were observed in 41 cases (58,6%), 36 cases (51,4%), and 48 cases (68,6%); respectively. Death was observed in four girls (5.7%) (p 0,034/OR 1,148/ 95% CI 1,003 - 1,315) with DSS because of severe condition on admission. Conclusions: Girl was an independent risk factor of death among children with DHF.